Tcf4 regulates secretory cell fate decisions in the small intestine and colon tumors: insights from transcriptomic, histological, and microbiome analyses - Janeckova, Lucie; Stastna, Monika; Hrckulak, Dusan; Berkova, Linda; Kubovciak, Jan; Onhajzer, Jakub; Kriz, Vitezslav; Dostalikova, Stela; Mullerova, Tereza; Vecerkova, Katerina; Tenglerova, Marketa; Coufal, Stepan; et al. (Stem cell research & therapy, 2025)
BACKGROUND: The canonical Wnt signaling pathway controls the continuous renewal of the intestinal epithelium and the specification of epithelial cell lineages. Tcf4, a nuclear mediator of Wnt signaling, is essential for the differentiation and maintenance of Paneth cells in the small intestine. Its deficiency is associated with reduced expression of key α-defensins, highlighting its role in host-microbe interactions. However, the exact function of Tcf4 in specifying the secretory lineage and its contribution to antimicrobial peptide production remain incompletely understood. Remarkably, α-defensin expression has also been detected in human colon adenomas, where aberrant Wnt signaling is a hallmark. This raises important questions: What is the role of these Paneth-like cells in tumor biology, and how does Tcf4 influence their identity and function? METHODS: We investigated cell specification in small intestinal crypts and colon tumors using conditional Tcf7l2 deletion, cell type-specific Cre recombinases, and reporter alleles in mice. Transcriptomic (single-cell and bulk RNA sequencing) and histological analyses were performed and complemented by microbiome profiling, antibiotic treatment, and intestinal organoids to functionally validate the main findings. RESULTS: The inactivation of Tcf4 depletes Paneth cells and antimicrobial peptides, disrupting the gut microbiota balance. In secretory progenitors, loss of Tcf4 shifts differentiation toward goblet cells. In the small intestine, alternative secretory progenitors produce Wnt ligands to support stem cells and epithelial renewal in the absence of Paneth cells. In colon tumors, Paneth-like cells form a tumor cell population, express Wnt ligands, and require Tcf4 for their identity. Loss of Tcf4 redirects their differentiation toward goblet cells. CONCLUSIONS: Tcf4 controls the balance between Paneth and goblet cells and is essential for antimicrobial peptide production in the small intestine. In colon adenomas, Paneth-like tumor cells drive antimicrobial gene expression and provide Wnt3 ligands, which may have implications for cancer therapy.
Keywords: buněčná diferenciace; Wnt Signaling Pathway; Gastrointestinal Microbiome; myši; Intestinal crypt; Animals; Intestinal cell lineage; Humans; Mice; Single-cell transcriptomics; pohárkové buňky; Colorectal cancer; Intestine, Small; Paneth Cells; signální dráha Wnt; transkripční faktor 4; Panethovy buňky; organoidy; Cell Differentiation; Paneth cells; Organoids; zvířata; Colonic Neoplasms; nádory tračníku; tenké střevo; Transcriptome; alpha-Defensins; transkriptom; Transcription Factor 4; lidé; Antimicrobial peptides; Goblet Cells; alfa-defensiny; střevní mikroflóra